The role of logistics infrastructure to attract foreign direct investment in Vietnam - Hoang Manh Hung; Le Thy Ha Van; Tran Thi Tung Quyen (My University, 2019)
The role of logistics infrastructure to attract foreign direct investment in Vietnam
Keywords: Logistics infrastructure; FDI attraction; Vietnam